VD_FINDINFO Décision / 2011 / 723 vom 14. November 2011 - VD Tribunal cantonal (2011)
EXPERTISE MÉDICALE, EXPERTISE, RÉCUSATION, DEMANDE ADRESSÉE À L'AUTORITÉ | 139 CPP (CH), 182 CPP (CH), 183 al. 3 CPP (CH), 184 CPP (CH), 393 al. 1 let. a CPP (CH), 56 CPP (CH)